Transcription factor WRKY46 regulates osmotic stress responses and stomatal movement independently in Arabidopsis. (5th June 2014) - Ding, Zhong Jie; Yan, Jing Ying; Xu, Xiao Yan; Yu, Di Qiu; Li, Gui Xin; Zhang, Shu Qun; Zheng, Shao Jian
Summary Drought and salt stress severely inhibit plant growth and development; however, the regulatory mechanisms of plants in response to these stresses are not fully understood. Here we report that the expression of a WRKY transcription factor WRKY46 is rapidly induced by drought, salt and oxidative stresses. T–DNA insertion of WRKY46 leads to more sensitivity to drought and salt stress, whereas overexpression of WRKY46 (OV46) results in hypersensitivity in soil‐grown plants, with a higher water loss rate, but with increased tolerance on the sealed agar plates. Stomatal closing in the OV46 line is insensitive to ABA because of a reduced accumulation of reactive oxygen species (ROS) in the guard cells. We further find that WRKY46 is expressed in guard cells, where its expression is not affected by dehydration, and is involved in light‐dependent stomatal opening. Microarray analysis reveals that WRKY46 regulates a set of genes involved in cellular osmoprotection and redox homeostasis under dehydration stress, which is confirmed by ROS and malondialdehyde (MDA) levels in stressed seedlings. Moreover, WRKY46 modulates light‐dependent starch metabolism in guard cells via regulating QUA‐QUINE STARCH (QQS) gene expression. Taken together, we demonstrate that WRKY46 plays dual roles in regulating plant responses to drought and salt stress and light‐dependent stomatal opening in guard cells.